PEMBUATAN DAN KARAKTERISASI KERTAS DARI CAMPURAN SERAT JAMBUL NANAS DAN SERAT JERAMI PADI - mufridayati mufridayati (Saintia Fisika, 2013)
The Research for making and characterization of paper has been made by using crested pineapple and straw fiber. The study was conducted to determine the optimum mixture of crested pineapple fiber and straw fiber composition that varied to 100%:0%,  80%:20%, 60%:40%, 40%:60%, 20%:80%, 0%:100%. Dried crested pineapple cooked by using 1,5 % NaOH with 225 gr in 100 0C. Dried rice straw  was cooked with by using 1,5 % NaOH in 100 0C. Then , the pulp was dried under the sun. The pulp was washed and whitening process with clorine and then it was washed and dried. After that the pulp was mixed according to the ratio, that have been made. The paper with composition of crested pineapple get the index 16.819 Nm / g and tear index is 3.046 x 10-3 Nm2 / g and this paper gramatur 61.24 g/m2. While the rice straw paper composition’s index gained 13.745 Nm / g and tear index 3.559 x 10-3 Nm2 / g. The optimum result of paper was the composition with 40%crested pineapple and the composition with60% rice straw fiber with tensile index 16.945 Nm / g and tear index was 3.719 x 10-3 Nm2 / g, according to the paper with SNI 14-1308-1998. Keywords: Fiber-crested Pineapple, Straw Fiber, Paper Making